Awareness Regarding Clean Green Pakistan through TV News Bulletin: A survey of University Students of Lahore - Ghani, Dr. Abdul; Khan, Hina; Cheema, Maryam Nazar (Journal of Professional Research in Social Sciences, 2022)
The purpose of this study is to analyze the current situation and factors for the environmental change worldwide. The sample size of this study was 300 respondents from three private sector universities of Lahore. Majority of the respondents are neutral that the electronic media play a significant role to promote the Clean Green Pakistan Movement. News bulletins of GEO, ARY and City 24 are creating awareness on Clean Green Pakistan. Time spent on Television comparatively shows the highest correlation with safe drinking water. University students practically take measures to act upon the CGPM after watching coverage